Pengaruh Penggunaan Aplikasi Kahoot! untuk Meningkatkan Retensi Materi Al-Qur’an dan Hadits serta Hasil Belajar Siswa di SMP Negeri 6 Singosari Malang - Nugroho, Rahmad Yoga; Wahidmurni, Wahidmurni; Wahyuni, Esa Nur (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
Low retention and academic achievement among students in the subject of Al-Qur’an and Hadith at SMP Negeri 6 Singosari Malang are attributed to the use of conventional teaching methods, low learning motivation, and students’ difficulties in memorizing and understanding texts. This study aims to: (1) describe students’ retention profiles and learning outcomes before and after the use of Kahoot! as a learning medium; (2) examine differences in learning outcomes between the experimental group using Kahoot! and the control group; and (3) assess differences in material retention between the two groups. A quasi-experimental method with a Posttest-Only Control Group design was employed, involving two Grade VII classes selected through simple random sampling: 32 students in the experimental group and 31 in the control group. The experimental group received game-based interactive learning using Kahoot!, while the control group received conventional instruction. Learning outcomes and retention were measured through posttests and analyzed both descriptively and inferentially using an independent samples t-test, following tests for normality and homogeneity (α = 0.05). The results showed that the experimental group achieved significantly higher mean scores in both retention (87.66; SD = 7.51) and learning outcomes (85.00; SD = 8.33) compared to the control group (retention: 75.00; SD = 11.90; learning outcomes: 70.65; SD = 12.23), with p < 0.001. These findings conclude that the use of Kahoot! significantly enhances students’ retention and academic achievement in Al-Qur’an and Hadith compared to conventional methods, demonstrating the effectiveness of technology-based interactive learning in religious education contexts.